The Integrating Role-playing into Board Games for History Education: Developing Non-digital Media to Boost Social Interaction - As Sayfullooh, Istiqomah; Irdamurni; Montessori, Maria; Bentri, Alwen; Marhadi, Agung; Latifah, Nafsi (MIMBAR PGSD Undiksha, 2024)
History education in primary schools should impart the noble values of the past, but it is often one-sided and lacks media, creating a passive and monotonous learning experience. This study aims to develop a non-digital board game integrated with role-playing features to promote the application of heroic values through social interactions among students. The research employed a Research and Development (R&D) design using the 4D development model. The development process involved four experts, four teachers, and 30 Phase C students (grades 5 and 6) from two elementary schools in Bukittinggi City and Agam Regency. Data were collected through observation sheets, interviews, and questionnaires. Based on expert evaluations during the Develop stage, the role-play-integrated board game achieved an average validity score of 90.2% for instructional aspects and 87.3% for technical media aspects. Quantitative testing during the Develop stage indicated high practicality, with average scores of 93.1% from student questionnaires and 94.5% from teacher questionnaires. In conclusion, the role-play-integrated board game developed in this study is deemed valid and practical for use in teaching history to Phase C students. Future research could examine the effectiveness of this board game in enhancing various social skills closely tied to social interaction, such as collaboration, competition, and others.